2019
DOI: 10.1093/jbcr/irz167
|View full text |Cite
|
Sign up to set email alerts
|

Utility of MolecuLight i:X for Managing Bacterial Burden in Pediatric Burns

Abstract: Pediatric burn injuries are vulnerable to severe complications, most often infection, making prompt and precise diagnosis of bacterial bioburden vital to preventing detrimental consequences and optimizing patients’ outcomes. Currently, burn wounds are assessed for infection via examining the clinical signs and symptoms of infection, which can be confirmed by swab culture analysis. While the former approach is subjective and experience-dependant, the latter technique is susceptible to missing subsurface, biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…In 10 of the 11 wounds assessed, bacterial fluorescence was detected (at loads >10 4 CFU/g) despite absence of CSS. These findings are in line with recent studies, [24][25][26] and confirm the ability of fluorescence imaging to detect presence of bacteria (at loads >10 4 CFU/g), in wounds asymptomatic for CSS. It is plausible that at 10 4 CFU/g, symptoms of infection may not manifest; but even at bacterial loads (>10 6 CFU/g) known to indicate infection, 8 fluorescence imaging has been shown to detect 50% more wounds than CSS assessment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In 10 of the 11 wounds assessed, bacterial fluorescence was detected (at loads >10 4 CFU/g) despite absence of CSS. These findings are in line with recent studies, [24][25][26] and confirm the ability of fluorescence imaging to detect presence of bacteria (at loads >10 4 CFU/g), in wounds asymptomatic for CSS. It is plausible that at 10 4 CFU/g, symptoms of infection may not manifest; but even at bacterial loads (>10 6 CFU/g) known to indicate infection, 8 fluorescence imaging has been shown to detect 50% more wounds than CSS assessment.…”
Section: Discussionsupporting
confidence: 91%
“…In a clinical trial of 50 hard-to-heal (chronic) wounds, Raizman et al reported fluorescence indicative of bacteria in the periwound of 89% of wounds 20 and Farhan et al detected bacteria in the peripheries of 88% of wounds. 25 However, we show here for the first time that the presence of periwound bacterial loads is associated with delayed healing and fluorescenceguided debridement of these regions to eliminate fluorescent signature from bacteria was associated with a shift of wounds onto a healing trajectory. Larger studies are warranted to better understand the potential detriment of bioburden harboured in periwound tissues, but these findings suggest that fluorescence imaging of hard-to-heal wounds can be used to enhance detection and targeted removal of bioburden in this region of the wound that is typically overlooked during routine assessment.…”
Section: Discussionmentioning
confidence: 62%
“…In line with preclinical studies, numerous observational studies and clinical trials have detected cyan fluorescence in wounds positive for PA ( Figure 1 c,d) [ 27 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Wound biopsies [ 27 , 46 ], curettage samples [ 45 ] or swabs [ 47 , 48 , 49 , 50 , 51 ] were collected for microbiological analysis to confirm the presence and amount of PA detected from cyan positive regions. In multiple instances, cyan fluorescence indicative of PA was detected in wounds otherwise lacking the typical signs of PA infection [ 27 , 44 , 46 ].…”
Section: Introductionsupporting
confidence: 77%
“…In an egg-based infection model, real-time fluorescence imaging detected cyan fluorescence indicative of PA, and this was used to assess the efficacy of antimicrobial treatments against PA [43]. In line with preclinical studies, numerous observational studies and clinical trials have detected cyan fluorescence in wounds positive for PA ( Figure 1c,d) [27,[44][45][46][47][48][49][50][51]. Wound biopsies [27,46], curettage samples [45] or swabs [47][48][49][50][51] were collected for microbiological analysis to confirm the presence and amount of PA detected from cyan positive regions.…”
Section: Evidence For Cyan Fluorescence Detected From Pseudomonas Aermentioning
confidence: 99%
“…Similarly, in a study of paediatric burns, contactless, painless, and immediate bacterial detection was possible using this fluorescence imaging device. In this patient population, rapid and effective wound disinfection is important to prevent septic progression . These user‐friendly aspects can also be confirmed by our clinical applications.…”
Section: Discussionsupporting
confidence: 60%